1995
DOI: 10.1029/95jb02035
|View full text |Cite
|
Sign up to set email alerts
|

Continuous GPS observations across the Hayward Fault, California, 1991–1994

Abstract: In September 1991, the U. S. Geological Survey began continuous operation of two permanent Global Positioning System (GPS) sites near the Hayward fault. We use two and one half years of data from an 8‐km baseline to investigate GPS processing strategies, errors in the time and frequency domains, and the uncertainties of rates of change calculated from such data. Experiments with session lengths show that at least 6 hours of data should be used to obtain a precision of 2 to 4 mm. Experiments with broadcast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…Deriving the noise values allow the authors to assess the time needed to detect a deformation rate with a certain confidence level. Thus, King et al (1995) have reported that for daily GPS observations with an instrument error or white noise of $3 mm (which matches nearly our value) a time span of 5 years of observations is necessary to accurately resolve a random-walk noise of 1 mm/year 1/2. The crucial part is determining the random-walk noise.…”
Section: Permanent Gps Station Networksupporting
confidence: 57%
See 1 more Smart Citation
“…Deriving the noise values allow the authors to assess the time needed to detect a deformation rate with a certain confidence level. Thus, King et al (1995) have reported that for daily GPS observations with an instrument error or white noise of $3 mm (which matches nearly our value) a time span of 5 years of observations is necessary to accurately resolve a random-walk noise of 1 mm/year 1/2. The crucial part is determining the random-walk noise.…”
Section: Permanent Gps Station Networksupporting
confidence: 57%
“…The baseline result could also easily be verified by EDM measurements. The comparison of two instruments allows to distinguish DEFORMATION ANALYSIS IN GERMANY common (e.g., monument) and independent noise sources (King et al, 1995) and thus quantify the monument effects. In any case, the method of the error analysis as outlined for the position time series is still advisable.…”
Section: Baselinesmentioning
confidence: 99%
“…Space geodetic techniques, particularly the Global Positioning System (GPS), now provide a great source of information about the patterns and rates of deformation across spatial scales of order 10 to 1000 km. Throughout the southwestern U.S. deformation zone, for example, continuously operating networks of GPS stations have been in operation since the mid‐1990s (e.g., International GPS Service (IGS) [ Beutler et al , 1994], Precision GPS Geodetic Array/Southern California Integrated GPS Network (PGGA/SCIGN) [ Bock et al , 1997; http://reason.scign.org], Bay Area Regional Deformation Network (BARD) [e.g., King et al , 1995], The Basin and Range Geodetic Network (BARGEN) [e.g., Bennett et al , 1998; Wernicke et al , 2000]). Further densification is provided by the many campaign sites from which data have become readily available [e.g., Bennett et al , 1997; Dixon et al , 2000a, 2000b; Gan et al , 2000; Miller et al , 2001; Shen et al , 1996; Thatcher et al , 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Although time series of daily position measurements from GPS exist, as discussed, for example, by King et al [1995], these measurements are currently about a factor of 3 less precise than the two-color measurements, and their time series are relatively short. In the future these GPS data will provide another means to measure monument instabilities.…”
Section: Introductionmentioning
confidence: 99%